Преимущества интенсификации теплообмена при проектировании теплообменных сетей - Арсеньева, Ольга Петровна; Товажнянский, Леонид Леонидович; Смит, Робин; Булатов, И. С.; Капустенко, Пётр Алексеевич; Хавин, Геннадий Львович (НТУ "ХПИ", 2012)
The mathematical model of plate heat exchanger with different geometrical parameters is considered. The optimization algorithm based on MINLP method with inequalities constraints is created. The heat transfer surface area of unit is considered as the objective function. The parameters of optimization are: the height of corrugation, the length of the plate, the corrugation angle to the vertical axis of the plate and the ratio of corrugation step to its height. The algorithm is implemented as DLL module that can be used for variety of calculations to optimize heat exchanger networks.
Keywords: теплообмен; теплообменное оборудование; вторичное тепло; кожухотрубные теплообменники; пластинчатые теплообменники; интенсификация; теплообменная сеть; математическая модель